THE INFLUENCE OF PEOPLE SATISFACTION ON SERVICES ORGANIZATION PUBLIC PERFORMANCE OF VILLAGE DISTRICTS IN SOUTH OF TANGERANG - Deni Surapto (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
A lack of bureaucracy community satisfaction in public service at the level of service and villages was the stigma impression of government apparatus received from the community for urban village. The residents’ satisfaction against public services from village influenced factor by responsiveness, credibility and empathy. Communities are satisfied with the services provided by officials in urban village, in providing services to the community. The method used in this research descriptive explanatory, are outlining and explaining the service, satisfaction toward society. The research survey used 200 respondents from 7 urban villages purposive through sampling methods and the kind of data supporting by primary and secondary data. Secondary data obtained and was gathered from various literature, book, a journal, the thesis and data from the internet that are considered relevant While the primary data was obtained through a method of surveying, namely by giving the research questionnaire in south of Tangerang. Instrument used in the analysis is spss and shem lisrel. Measurement of data done in this research used 1-5 likert scale. The results of this research proves that people feel that the officers being disciplined in providing services (x25), officers will always be in place to provide services (x26), in addition they felt easy to contact officers (x29). Some people feel the counter complaints service in the form of suggestions box just a display there have been no a follow-up (x33). The first hypothesis is: the impact on service satisfaction (accepted; 2.31>1,96). They felt the officers have to work in accordance with discipline time (x34). The target completion of conformity work received after the resident complained (x36) dependability and residents see the officers in (x39) does the work, in addition the officers can work together with colleagues (x40), and also has the initiative in work (x41). But, on the other hand, in carrying out the work, residents still seeing officers has not been fully worked with neat and minutely (x35). From this research, it can be concluded that the performance impact on the satisfaction of (the second hypothesis is accepted; 3,21> & gt; 1,96). The employees of services provided include the urban population and civil registration (Dukcapil) in south of tangerang, the people are satisfied with the services provided by employees urban village.